DESIGN AND BUILD AUTOMATIC FISH FEEDING DEVICE BASED ON INTERNET OF THINGS - Saifullah, Afif Pandu (Universitas Lampung, 2024)
Generally, living organisms can be considered healthy when their nutritional intake and overall nutrition are well satisfied. This applies not only to humans and plants but also to the growth and development of animals, which are influenced by regular feeding and drinking patterns, especially for pets. Feeding pets regularly can sometimes become a serious issue faced by every pet owner. Some factors contributing to feeding problems include lack of time for caretaking, forgetfulness about feeding times, laziness in pet care, limited availability of food, and mismatched types of food for the pets. This research aims to assist in feeding fish at Gajah Tunggal Polytechnic. The design of this research is carried out using the Research & Development (R&D) method, which involves the process of creating and developing a system based on research conducted, ranging from system planning to its practical implementation.